2014
DOI: 10.3390/nu6072973
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Arthrospira platensis Capsules on CD4 T-Cells and Antioxidative Capacity in a Randomized Pilot Study of Adult Women Infected with Human Immunodeficiency Virus Not under HAART in Yaoundé, Cameroon

Abstract: Dietary supplements are often used to improve the nutritional status of people living with HIV/AIDS (PLHIV). Arthrospira platensis (Asp), also known as Spirulina, is a cyanobacterium rich in proteins and micronutrients. Cell and animal trials described immune-modulating, antiretroviral and antioxidant activities. This pilot study describes the effects of the supplementation of 5 g/day of Asp on a pre-highly-active antiretroviral therapy (pre-HAART), HIV-infected, adult female population. It was conducted as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
2
22
0
1
Order By: Relevance
“…The findings in the present study are consistent with those in previously established reports of an increase in antioxidant capacity when Spirulina is administered [25,57]. Likewise, the concentrations of the GSSG at the end of the treatment period in the group SM, suggests an increase in the activity of glutathione peroxidase; this contribution of GSH in patients treated with SM could also explain the decrease in the activity of glutathione reductase, a fact that is described in the context of glutathione metabolism [58].…”
Section: Antioxidant Statussupporting
confidence: 92%
See 2 more Smart Citations
“…The findings in the present study are consistent with those in previously established reports of an increase in antioxidant capacity when Spirulina is administered [25,57]. Likewise, the concentrations of the GSSG at the end of the treatment period in the group SM, suggests an increase in the activity of glutathione peroxidase; this contribution of GSH in patients treated with SM could also explain the decrease in the activity of glutathione reductase, a fact that is described in the context of glutathione metabolism [58].…”
Section: Antioxidant Statussupporting
confidence: 92%
“…SM has shown to have antioxidant properties in both in vivo and in vitro studies [44][45][46][47][48][49][50][51][52][53][54][55]. In addition, it has also shown to have an antioxidant effect in several clinical studies: for example, in patients with human immunodeficiency virus infection, the administration of SM increases the antioxidant capacity in plasma [25]; in older adults it increases the antioxidant capacity [56]; increases the ergogenic and antioxidant capacity in athletic subjects [57]. However, there are no publications that indicate the effect of SM on the antioxidant status of patients with systemic arterial hypertension.…”
Section: Antioxidant Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ability to enhance the internal antioxidant defense system (Miranda et al 1998;BermejoBescós et al 2008) has also been demonstrated. Although there is not a clinical report that shows a clear effect of SP as a neuroprotective agent, there are clinical studies that report SP use as immunomodulatory (Pugh et al 2001;Hirahashi et al 2002;Winter et al 2014). Interestingly, SP has been admitted as dietary supplement ingredients in the United States Pharmacopeia (Marles et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Winter et al (2014) conducted an in vivo study on 73 HIV-infected women to evaluate Arthrospira supplementation effect. The study was a three-month pilot, randomized, double-blind and placebo-controlled intervention.…”
Section: Algae and Antiviral Activitiesmentioning
confidence: 99%